KOMPETENSI ORANGTUA DALAM BERKOMUNIKASI UNTUK MEMBERIKAN PEMAHAMAN TENTANG SEKS KEPADA ANAK - Eliza Nurjannah; Sri Eko P. (Program studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Persada Indonesia YAI, 2021)
The background of this study that the researchers decided rampant free sex performed by a number of teens. Researchers would like to develop the concept of this communication kompetenisi into the family, especially to parents. It would require good communication competence of the parents themselves so parents can provide insight to children about sex. The purpose of this communication competence is to know how the parent's ability to provide an understanding of sex to their children. In conducting this study, researchers refer to the concept of interpersonal communication, the concept of verbal communication, non-verbal, understanding the concept of sex, the concept of the family, the concept of the child, and the theory of self-disclosure. This study used a qualitative approach that is qualitative descriptive. The unit of analysis was the parent and child as well as individuals who are considered directly related to the research topic. And data collection techniques, namely through the process of in-depth interviews and non-participant observation, as well as through the study of literature and documents study, researchers used triangulation to test triangulation. The results of this study show that not all parents have the competence in communicating about sex to their children, each parent has a communication styles vary in communicating it to his son. Some are able to communicate well, and there are parents who simply deliver it when asked, but most of them can deliver when there is a picture that provoke them to explain, for example, when a child asks also news about the rape, and the reality in the neighborhood that a lot of children women who are pregnant out of wedlock. So therefore, we conclude that the concept of communication and the theory of self-disclosure can be applied to determine how the ability of parents and the openness of parents in providing an understanding of the child's sex.